Factors that Affected Pregnant Womans to Do Ultrasonographic Test During Pregnancy - Novita Alfiani; Halinda Fatmayanti; Rinayati Rinayati (Indonesian Journal of Global Health Research, 2022)
Pregnancy check-ups are mandatory for pregnant women to know the progress of pregnancy, the level of health of the womb, the condition of the fetus, and even diseases or abnormalities in the womb that are expected to be treated early. As many as 99% of maternal and infant deaths due to labor or birth problems occur in developing countries, while the maternal mortality rate (MMR) and infant mortality rate (IMR) are caused by pregnancy complications, pregnancy complications and this is due to low visits by pregnant women (Antenatal Care). so that these complications are not detected early. One of these services is an ultrasound examination, which is an examination carried out if there is an indication, then an ultrasound examination is carried out to determine the presence of complications in pregnancy. Examination using ultrasound is seen as one of the methods of examination that is safe, practical, and the results are accurate enough to detect complications early. The purpose of this study was to find out what factors can influence pregnant women to perform ultrasound examinations including maternal knowledge, family support and support from health workers. This research is an analytic correlation study with a cross sectional approach. The sample consisted of 62 pregnant women respondents. As a data collection tool used a questionnaire sheet. Data analysis using bivariate analysis with chi square test with the results of the r value on the question item above 0.05. From the results of the study, it was found that there was a significant influence between the level of knowledge, p value = 0.001, family support factor p value = 0.004, health worker factor p value = 0.020 with the choice of ultrasound examination with a value (p < 0.05). It can be concluded that the level of knowledge, family support factors, health workers factors affect the motivation of pregnant women to check their pregnancy using ultrasound.